2022
DOI: 10.1111/php.13724
|View full text |Cite
|
Sign up to set email alerts
|

UV Inactivation of Common Pathogens and Surrogates Under 222 nm Irradiation from KrCl* Excimer Lamps

Abstract: Germicidal ultraviolet (UV) devices have been widely used for pathogen disinfection in water, air, and on food and surfaces. Emerging UV technologies, like the krypton chloride (KrCl*) excimer emitting at 222 nm, are rapidly gaining popularity due to their minimal adverse effects on skin and eyes compared with conventional UV lamps emitting at 254 nm, opening opportunities for UV disinfection in occupied public spaces. In this study, inactivation of seven bacteria and five viruses, including waterborne, foodbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 58 publications
1
22
1
Order By: Relevance
“…This phenomenon is consistent with previous reports 36,69−71 and is likely attributed to the protection of bacterial genome by the cell wall and plasma membrane, which contain proteins and other biomolecules that have higher absorbance at 222 nm than 254 nm. 36 Moreover, the shoulder length of the inactivation curve by UV 222 (2.41−2.69 mJ cm −2 ) was shorter than that by UV 254 (3.25−3.57 mJ cm −2 ) (p = 0.01), likely due to the stronger attack of UV 222 than UV 254 on the protein of the cells. 7,72 The lag phase of bacteria inactivation during UV disinfection is caused by the self-repair of the bacteria mediated by various enzymes (e.g., photolyase and DNA glycosylases).…”
Section: Nitrate Significantly Inhibits E Colimentioning
confidence: 90%
“…This phenomenon is consistent with previous reports 36,69−71 and is likely attributed to the protection of bacterial genome by the cell wall and plasma membrane, which contain proteins and other biomolecules that have higher absorbance at 222 nm than 254 nm. 36 Moreover, the shoulder length of the inactivation curve by UV 222 (2.41−2.69 mJ cm −2 ) was shorter than that by UV 254 (3.25−3.57 mJ cm −2 ) (p = 0.01), likely due to the stronger attack of UV 222 than UV 254 on the protein of the cells. 7,72 The lag phase of bacteria inactivation during UV disinfection is caused by the self-repair of the bacteria mediated by various enzymes (e.g., photolyase and DNA glycosylases).…”
Section: Nitrate Significantly Inhibits E Colimentioning
confidence: 90%
“…The UV sensitivity of Phi6 in this study was similar to that of MS2 in a previous study, which reported that the UV action spectrum of MS2 peaked at about 260 nm and featured a minimum of approximately 240 nm, and MS2 was most sensitive to lower wavelengths below 230 nm. This is due to the strong absorption maximum of proteins at 222 nm. , The lower wavelengths did not increase bacterial inactivation relative to inactivation at 254 nm, which indicated that a higher UV dose is required at 222 nm than 254 nm for the same bacterial inactivation . The bacterial sensitivity strongly fit the absorption curve of nucleic acids, and the curve of the inactivation rate constant, a function of the UV wavelength, did not depend on the bacterial species.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, the disinfection efficacy of UV-LEDs or excimer lamps for target microorganisms can be as effective as or better than conventional mercury lamps at a given wavelength and dose combination, i.e., lower doses are required for equivalent disinfection . Wavelengths below 240 nm are thought to be more effective in inactivating specific pathogens. Moreover, 222 nm UV showed better inactivation efficiency against non-enveloped viruses (e.g., MS2 coliphage and adenovirus) and enveloped viruses (bacteriophage Phi6 and coronavirus) than other UVC. , However, little is known about the UVC-induced inactivation mechanisms of enveloped viruses, especially at 222 nm, compared to non-enveloped viruses. In addition to their high inactivation efficiency, conventional LP-Hg, and MP-Hg lamps have been widely utilized in water treatment, primarily owing to their high wall-plug efficiency (30–35 and 10–20%, respectively) .…”
Section: Introductionmentioning
confidence: 99%
“…A number of laboratories have shown that, when far-UVC is used within current regulatory limits, it has a high germicidal efficacy 6,45 particularly for airborne pathogens, and represents minimal short-and long-term risk to skin and eyes 20,23,26 . Thus, whole room far-UVC is a promising technology to reduce transmission of infectious diseases in human-occupied spaces 32,33,39 .…”
Section: Discussionmentioning
confidence: 99%